2017
DOI: 10.3389/fcimb.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold of Selenium Nanovectors and Honey Phytochemicals for Inhibition of Pseudomonas aeruginosa Quorum Sensing and Biofilm Formation

Abstract: Honey is an excellent source of polyphenolic compounds that are effective in attenuating quorum sensing (QS), a chemical process of cell-to-cell communication system used by the opportunistic pathogen Pseudomonas aeruginosa to regulate virulence and biofilm formation. However, lower water solubility and inadequate bioavailability remains major concerns of these therapeutic polyphenols. Its therapeutic index can be improved by using nano-carrier systems to target QS signaling potently. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…When P. aeruginosa PAO1 was cultivated in the presence 5 Journal of Nanomaterials of sub-MICs of TONFs, elastase activity was suppressed significantly to 59% and protease production was reduced up to 64% as compared to untreated control (Figure 8). Prateeksha et al [50] reported a comparable decrease in elastase (52%) and protease (60%) after treatment with sub-MICs of selenium nanovectors.…”
Section: Effects Of Tonfs On Quorummentioning
confidence: 94%
“…When P. aeruginosa PAO1 was cultivated in the presence 5 Journal of Nanomaterials of sub-MICs of TONFs, elastase activity was suppressed significantly to 59% and protease production was reduced up to 64% as compared to untreated control (Figure 8). Prateeksha et al [50] reported a comparable decrease in elastase (52%) and protease (60%) after treatment with sub-MICs of selenium nanovectors.…”
Section: Effects Of Tonfs On Quorummentioning
confidence: 94%
“…A delivery system based on varnishes releasing the QSI thiazolidinedione-8 (TZD-8) was used on catheters and were active against Candida albicans biofilms (Shenderovich et al, 2015 ). Notably, honey polyphenols were introduced into a scaffold of selenium nanovectors for quenching P. aeruginosa PAO1 in vitro and in vivo (Prateeksha et al, 2017 ).…”
Section: Use Of Quorum Quenching Molecules In Medical Devicesmentioning
confidence: 99%
“…Honey was tested in vitro against aerobic bacteria such as; S. aureus [28]; MRSA [29][30][31]; E. coli [32]; S. typhimurium [33]; Klebsiella pneumonia [34]; Ps. Aerugenosa 35 and anaerobic Porphyromonas gingivalis [36]. Also its antifungal activity against Candida sp.…”
Section: Discussionmentioning
confidence: 99%